Characterization of canine adipose- and endometrium-derived Mesenchymal Stem/Stromal Cells and response to lipopolysaccharide - Phyo, Hlaing; Aburza, Amira; Mellanby, Katie; Esteves, Cristina L. (Frontiers in Veterinary Science, 2023)
Mesenchymal Stem/Stromal Cells (MSCs) are used for regenerative therapy in companion animals, namely in the dog. Their potential was initially attributed to multipotency, but subsequent studies in rodents, humans and veterinary species evidenced that MSCs produce factors that are key mediators of immune, anti-infective and angiogenic responses, which are key properties in tissue repair. MSCs preparations have been classically obtained from bone marrow and adipose tissue (AT) in live animals, what requires the use of surgical procedures. In contrast, the uterus, which is naturally exposed to external insult and infection, can be accessed nonsurgically to obtained samples, or tissues can be obtained after neutering. In this study, we explored the endometrium (EM) as an alternative source of MSCs, which we compared with AT obtained from canine paired samples. Canine AT- and EM-MSCs, formed CFUs when seeded at low density, underwent tri-lineage differentiation into adipocytes, osteocytes and chondrocytes, and expressed the CD markers CD73, CD90 and CD105, at equivalent levels. The immune genes IL8, CCL2 and CCL5 were equally expressed at basal levels by both cell types. However, in the presence of the inflammatory stimulus lipopolysaccharide (LPS), expression of IL8 was higher in EM- than in AT-MSCs (P<0.04) while the other genes were equally elevated in both cell types (P<0.03). This contrasted with the results for CD markers, where the expression was unaltered by exposing the MSCs to LPS. The results indicated that canine EM-MSCs could serve as alternative to AT-MSCs. The distinct EM-MSCs immune features could be advantageous in therapeutic applications.